1981
DOI: 10.1038/clpt.1981.34
|View full text |Cite
|
Sign up to set email alerts
|

Methadone binding to orosomucoid (α1-acid glycoprotein): Determinant of free fraction in plasma

Abstract: The distribution of basic drugs in blood differs qualitatively from that of acidic drugs. The binding of racemic, d-methadone, and l-methadone to human plasma and isolated protein fractions was studied by equilibrium dialysis at 37 degrees. In plasma samples from 29 healthy subjects free fraction of dl-methadone was (mean% +/- SD) 10.62 +/- 1.43. There were significant variations among subjects (p less than 0.001). The free fraction of the d-isomer was 9.24 +/- 1.61% and of the l-isomer, 12.44 +/- 1.53%. Plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(38 citation statements)
references
References 1 publication
4
33
0
1
Order By: Relevance
“…In the current study, a negative relationship was observed between AGP concentrations and the unbound (active) percentage of R-methadone, similar to previously reported findings (20). As shown by the parallel decreasing slopes of the linear regression lines in Fig.…”
Section: Discussionsupporting
confidence: 78%
“…In the current study, a negative relationship was observed between AGP concentrations and the unbound (active) percentage of R-methadone, similar to previously reported findings (20). As shown by the parallel decreasing slopes of the linear regression lines in Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Aprindine (Teirlynck et al, 1982) Bupivacaine (Denson et al, 1984) Disopyramide (Lima et al, 1981) Lignocaine (Routledge et al, 1980a) Pirmenol (Hammill et al, 1982) Quinidine (Nilsen et al, 1978) Verapamil (McGowan et al, 1983) Opiates Methadone (Romach et al, 1981) Pethidine (Nation, 1981) Antidepressants Amitriptyline (Pike & Skuterud, 1982) Imipramine Nortriptyline (Pike & Skuterud, 1982) Variability in protein binding…”
Section: Antiarrhythmicsmentioning
confidence: 99%
“…The pharmacologic effect of these agents is proportional to the plasma total drug concentration (3,4). The clinical interpretation of plasma drug levels is complicated by the fact that many basic lipophilic drugs are bound by a plasma globulin, orosomucoid, i.e., a,-acid glycoprotein (5)(6)(7). Orosomucoid is an acute-phase reactant and serum levels of this protein rise severalfold in a variety of inflammatory illnesses (8).…”
Section: Introductionmentioning
confidence: 99%